2013
DOI: 10.3389/fgene.2013.00182
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic modulation of chromatin: implications for DNA repair and genomic integrity

Abstract: The maintenance of genomic integrity in response to DNA damage is tightly linked to controlled changes in the damage-proximal chromatin environment. Many of the chromatin modifying enzymes involved in DNA repair depend on metabolic intermediates as cofactors, suggesting that changes in cellular metabolism can have direct consequences for repair efficiency and ultimately, genome stability. Here, we discuss how metabolites may contribute to DNA double-strand break repair, and how alterations in cellular metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 110 publications
(165 reference statements)
0
28
0
Order By: Relevance
“…Alterations in NAD + levels modulate DNA repair and NAD + is elevated under conditions of nutrient deprivation. NAD + -dependent P enzymes [poly(ADP-ribose) polymerase (PARP)1 and PARP2] are immediately activated in response to DNA DSBs and function to regulate both nonhomologous end joining and homologous recombination (30). In our study, PARP1 gene expression was shown to be elevated in fasted etoposide-treated mice compared with their fed counterparts (Dataset S2).…”
Section: Crypt Stem Cells Maintain Integrity Of the Si In Fasted Micementioning
confidence: 68%
See 1 more Smart Citation
“…Alterations in NAD + levels modulate DNA repair and NAD + is elevated under conditions of nutrient deprivation. NAD + -dependent P enzymes [poly(ADP-ribose) polymerase (PARP)1 and PARP2] are immediately activated in response to DNA DSBs and function to regulate both nonhomologous end joining and homologous recombination (30). In our study, PARP1 gene expression was shown to be elevated in fasted etoposide-treated mice compared with their fed counterparts (Dataset S2).…”
Section: Crypt Stem Cells Maintain Integrity Of the Si In Fasted Micementioning
confidence: 68%
“…Many of the chromatin-modifying enzymes involved in DNA repair depend on metabolic intermediates as cofactors for their activity, thereby directly linking changes in cellular metabolism with DNA repair (30). Interestingly, high levels of NAD + (nicotinamide adenine dinucleotide) correlate with radioprotection of human glioma cells (31).…”
Section: Crypt Stem Cells Maintain Integrity Of the Si In Fasted Micementioning
confidence: 99%
“…The importance of accumulated DNA damage in ageing is illustrated by several progeroid phenotypes, which are induced by mutations in DNA repair enzymes 136 , although it is unclear whether increased DNA repair itself can extend lifespan. Interestingly, metabolites linked to the regulation of longevity, such as NAD or α-ketoglutarate, modulate the activity of proteins involved in both DNA repair and chromatin remodeling 137 . For example, the recruitment of NAD-dependent deacetylases SIRT1 and SIRT6 may directly promote genomic stability 69, 70, 73, 74 .…”
Section: Epigenetics and Genomic Stability In Ageingmentioning
confidence: 99%
“…Epigenetic modifications play a major role in tissue- and cell-type-specific differences in gene expression (100, 138) and many other cellular processes (73, 131, 137). The role of epigenetics in disease is well established in the field of cancer (10, 34) and imprinting disorders (8).…”
Section: Figurementioning
confidence: 99%